PEMBELAJARAN INTERAKTIF BERBANTUAN GOOGLE SITES DENGAN MODEL PJBL UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI PESERTA DIDIK - Tesa Indita Sari (Universitas Muhammadiyah Purwokerto, 2023)
Collaboration skills are one of the soft skills that must be possessed by vocational students. When collaborating, contributions of thoughts or ideas will emerge from students and foster responsibility for the results obtained. PjBL is a learning model that is currently being prioritized, Google Sites learning media is a learning media that is still not much developed. Based on this, this study aims to determine the application of Project-based Learning-based interactive learning with the help of Google Sites in improving students' collaboration skills in the Basic Chemistry Analysis subject. This research is a Classroom Action Research conducted in 2 cycles. The research instrument is in the form of observation and performance appraisal. Of the 6 indicators of collaboration skills, there was an average increase from pre-cycle of 51.3% (enough), cycle I of 78.1% (good) and cycle II of 85.8% (very good). There is an increase in performance and product assessments produced by students in cycle I and cycle II. The average percentage in cycle I was 70.9% and in cycle II was 83.7%. So, the learning model of Project Based Learning Assisted with interactive learning media with Google Sites is able to improve students' collaboration skills.